Juridical Review on Termination of Employment As the Company is in the State of Postponing Its Debt Payment Obligation - Muhammad Hafidz (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2021)
In an unavoidable circumstance, the work relation between a worker/a labor and an employer can be ended. The imbalance in socio and economic positions places the state, as a regulator and at the same time as a supervisor for the statutory provisions that the limits of permissible particular circumstances that might lead to termination of employment. Those particular circumstances can be found in Law No 11 of 2020 on the Job Creation and its implementing regulations. There is a circumstance under the law that may lead to termination of employment; one of them is a company in the state of postponing a debt payment obligation. The provision is based on Law No 37 of 2004 on the Bankruptcy and Postponement of Debt Payment Obligations. Is this circumstance being appropriate reason for an employer to terminate employment? This research applies a normative judicial methodology based on comparative law. The data used are secondary data from documents. All collected data are processed and analyzed to find the legal issues that later become the object of this research and presented descriptively afterward. The research shows that the postponing debt payment obligation status is an inappropriate reason to terminate employment because that status is actually an opportunity provided for a company to avoid bankruptcy so that the company can operate as usual.